Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
x = 1 ; y = 3
Step-by-step explanation:
[tex]4x + y = 7 \\ y = 7 - 4x[/tex]
Now we know the value of y is 7 - 4x we plug this value to the second equation with y, So,
[tex]3x + 2(7 - 4x) = 9 \\ 3x + (14 - 8x) = 9 \\ - 5x = 9 - 14 \\ - 5x = - 5 \\ x = \frac{ - 5}{ - 5} \\ x = 1[/tex]
Now to find the value of y we use the first equation
[tex]y = 7 - 4x \\ y = 7 - 4(1) \\ y = 7 - 4 \\ y = 3[/tex]
Hope this helps you :)
Answer:
x = 6/5 or 1.2 y = 11/5 or 2.2
Step-by-step explanation:
4x + y = 7
y = -4x + 7
y = 7 - 4x
3x + 2y = 9
3x + 2(7 - 4x) = 9
3x + 14 - 8x = 9
-5× + 15 = 9
-5x = 9 - 15
-5x = -6
x = -6/-5
x = 6/5
4x + y = 7
4(6/5) + y = 7
24/5 + y = 7
y = 7 - 24/5
y = 35/5 - 24/5
y = 11/5
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.